Law & justice in Australia - Vines, Prue (Oxford University Press, 2005)
Law and Justice in Australia takes an historical, critical and contextual approach to law and justice and offers students a mix of stories, cases. article extracts and explanatory commentary with which to engage with the Australian Legal System. Together with the author's natural narrative writing style the book encourages students to develop an in-depth understanding of the legal system and creates a sound basis for further law study